Design and synthesis of small molecule inhibitors of coagulation FXIIa - Chen, Xi (2018)
Blood coagulation factors, factor XII (FXII), plasma kallikrein (PK), factor XI (FXI), and high-molecular-weight kininogen (HMWK), are four proteins that are involved in the plasma contact activation system (CAS) and kallikrein-kinin system (KKS). FXII is the initiation point of the intrinsic pathway of blood coagulation and is also the link between procoagulant and proinflammatory reactions. A number of inhibitors for blood coagulation factors have been approved for clinical usage. These inhibitors not only show inhibitory activities against thrombosis, but also disrupt haemostasis causing excessive bleeding. Contrasted with other coagulation proteases, the deficiency in FXII, instead of causing excessive bleeding, only reduces thrombus formation in blood coagulation. This unique property has made FXII a potential target for the treatments of thrombosis. FXII inhibitors such as aptamers, antibodies and peptides have been reported. Due to their limitations, some inhibitors have poor selectivity or weak binding affinity. Some inhibitors (biopolymers) have pharmaceutical problems. A chemically synthesised FXII inhibitor, with high selectivity is of great importance. The current lack of small molecule FXII inhibitors is limiting efforts to fully understand and validate FXII as a drug target. This project aims to design and synthesise a novel class of 1, 2, 5-tri-substituted benzene urea compounds as potent FXIIa inhibitors. Using Lossen rearrangement, a total of 134 urea compounds were chemically synthesised in this project. All compounds were biologically tested against activated factor XII (FXIIa). Detailed structure-activity relationships (SAR) information was obtained by functional enzyme assays (FXIIa). The range of activity of urea lead compounds in series is between 5.7 μM and 182.0 μM. The urea compound (127) bearing a benzamidine functional group (4-((2-(3-(2-(Pyrrolidin-1-yl)-5-(trifluoromethyl)phenyl)ureido)ethyl)sulfonamido)benzamidine) had the most potent inhibition against FXIIa (α-FXIIa: 5.7 ± 0.1 μM; β-FXIIa: 5.9 ± 0.2 μM). The top 25 most potent inhibitors were selected and were biologically tested for their selectivity between FXIIa and activated factor X (FXa). There are four out of 25 compounds showed their activities against FXa in a range between 1.9 ± 0.6 μM and 141.7 ± 16.5 μM. The selectivity between FXa and FXIIa was rationalised by serine protease-ligand crystal structure (FXa-rivaroxaban complex) and computational modelling simulation (FXIIa-hybrid model). In conclusion, potent FXIIa inhibitors were identified. The present study provides a rationale for further development of FXIIa inhibitors for the treatment of thrombosis and the investigation of selectivity between FXIIa and factor Xa (FXa).